The Legal Limits of Peacemaking in the Politics of the Iberian Peninsula in the Late Middle Ages: the Validity of Diplomatic Agreements (Edad Media. Revista de Historia, 2024)
Diplomatic treaties were the main instruments available to late medieval diplomacy to shape the rules of the political game in periods of peace between two sovereigns. We intend to elucidate to what extent these treaties in the Iberian context had sufficient force to be relevant in the political game, and wether we can speak of the existence of a law of treaties and, ultimately, of a public international law. With the analysis of the treaties and other sources, we have observed a horizon in which there was a de facto regulation in which aspects such as validity, observance, confirmation, renegotiation, and the question of the legitimacy of a rupture were contemplated.
Keywords: Diplomacy; Diplomatics; Peacemaking; Late Middle Ages; Iberian Peninsula